Indications, Complications, and Outcomes of Cardiac Surgery After Heart Transplantation: Results From the Cash Study - Gökler, Johannes; Aliabadi-Zuckermann, Arezu Z.; Kaider, Alexandra; Ambardekar, Amrut V.; Antretter, Herwig; Artemiou, Panagiotis; Bertolotti, Alejandro M.; Boeken, Udo; Brossa, Vicens; Copeland, Hannah; Generosa Crespo-Leiro, Maria; Eixerés-Esteve, Andrea; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Allograft pathologies, such as valvular, coronary artery, or aortic disease, may occur early and late after cardiac transplantation. Cardiac surgery after heart transplantation (CASH) may be an option to improve quality of life and allograft function, and to prolong survival. Experience with CASH, however, has been limited to single center reports. Methods: We performed a retrospective, multicenter study of heart transplant recipients with CASH between January 1984 and December 2020. Sixty high-volume cardiac transplant centers were invited to participate. Results: Data were available from 19 centers in North America (n=7), South America (n=1), and Europe (n=11), with a total of 110 patients. A median of 3 (IQR 2–8.5) operations were reported by each center; five centers included ≥10 patients. Indications for CASH were valvular disease (n=62), coronary artery disease (n=16), constrictive pericarditis (n=17), aortic pathology (n=13), and myxoma (n=2). Median age at CASH was 57.7 (47.8–63.1) years with a median time from transplant to CASH of 4.4 (1–9.6) years. Reoperation within the first year after transplantation was performed in 24.5%. In-hospital mortality was 9.1% (n=10). One-year survival was 86.2% and median follow-up 8.2 (3.8–14.6) years. The most frequent perioperative complications were acute kidney injury and bleeding revision in 18% and 9.1%, respectively. Conclusions: CASH has low in-hospital mortality and postoperative complications in carefully selected patients. The incidence and type of CASH varies between international centers. Risk factors for worse outcome are older age at CASH, higher EuroSCORE II, urgent indication and postoperative renal failure.